A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 TUALANG IN WRITING DESCRIPTIVE TEXTS - Suharni, Mery; Gultom, Effendy; ', M. Nababan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is to find out the ability of the second year students of SMAN 1 Tualang in writing descriptive texts. In this research, the data was obtained from students’ writing scores. The test is in the form of an essay because the test required the respondents to give the answer in the form of written descriptive text. There are five components of writing: grammar, organizing ideas, vocabulary, fluency / content, and mechanics (Harris : 1974). The writer analyzed the ability of the second year students based on five category: excellent, good, mediocre, poor, and very poor. The participants in this study are 26 students from XI IPA2 of SMAN 1 Tualang. The result of this study described that a number of students faced a problem in mechanics. Grammar is the highest average score. Based on these findings, it can be concluded that the ability of the second year students of SMAN 1 Tualang is in good level. Although the students still faced some difficulties in writing descriptive texts.Key words: writing ability, descriptive text